2022
DOI: 10.26444/aaem/150273
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Polish adolescents towards energy drinks. Part 1. Development, validation and reliability testing of a scale to identify attitudes towards energy drinks

Abstract: Żyłka K, Ocieczek A. Attitudes of Polish adolescents towards energy drinks. Part 1. Development, validation and reliability testing of a scale to identify attitudes towards energy drinks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…It is worth mentioning that among such studies were research papers that aimed to identify attitudes towards EDs. However, as has been shown in the first part of the present paper [34], authors of the cited studies have failed to identify these attitudes. Therefore, a substantive and research gap has been found in the issue of attitudes towards EDs.…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…It is worth mentioning that among such studies were research papers that aimed to identify attitudes towards EDs. However, as has been shown in the first part of the present paper [34], authors of the cited studies have failed to identify these attitudes. Therefore, a substantive and research gap has been found in the issue of attitudes towards EDs.…”
Section: Introductionmentioning
confidence: 61%
“…The study aimed to identify adolescents' attitudes towards EDs, and to investigate associations between these attitudes and ED consumption behaviours. Attitudes towards EDs were identified based on a scale which was developed, validated and tested by the authors in terms of reliability [34]. The study also aimed to assess whether attitudes and ED consumption behaviours were differentiated by variables, such as gender, stage of education, socio-economic status and academic achievement.…”
Section: Objectivementioning
confidence: 99%
See 1 more Smart Citation
“…The FNS and VARSEEK scales used in the study have been translated into Polish and edited and validated by Żyłka and Ocieczek [24]. The use of the FNS and VARSEEK scales in the study was not accidental.…”
Section: Methodsmentioning
confidence: 99%